2018
DOI: 10.1002/adsp.12062
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Education-Related Needs of Contemporary Male Veterans

Abstract: Fifteen male veteran college students participated in a qualitative study examining the challenges they experienced while adjusting to college and the supports that facilitated their transitions. Responses revealed 5 common themes: academic challenges; reluctance to seek assistance; difficulty connecting with faculty, staff, and other students; difficulty finding balance in life; and the value of veterans centers on campus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…In particular, student veterans with a strong military core as part of their personal identities, those with combat experience, and veterans with longer lengths of military service may hesitate to connect to being college students. This is consistent with extant research in the field (ASHE, 2011;Atuel & Castro, 2018;Carne, 2011;Jones, 2013;Killam & Degges-White, 2018;Lostutter et al, 2020;Olsen et al, 2014;Smith & True, 2014). As Atuel and Castro (2018) explained:…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, student veterans with a strong military core as part of their personal identities, those with combat experience, and veterans with longer lengths of military service may hesitate to connect to being college students. This is consistent with extant research in the field (ASHE, 2011;Atuel & Castro, 2018;Carne, 2011;Jones, 2013;Killam & Degges-White, 2018;Lostutter et al, 2020;Olsen et al, 2014;Smith & True, 2014). As Atuel and Castro (2018) explained:…”
Section: Discussionsupporting
confidence: 85%
“…The 10 undergraduate student veteran participants range in personal, service-related, and college demographics, and they discuss the degree to which they affiliate their own identities to those of typical servicemembers, student veterans, and college students. Data from these interviews support prior work engaging student veteran identity that finds the identity negotiation of student veterans is more complex than we may think (Atuel & Castro, 2018;Killam & Degges-White, 2018;Phillips & Lincoln, 2017). Further still, this study's findings reveal that many student veterans are acutely aware of the identity negotiations taking place as they move from the service through college and into post-college employment.…”
Section: Researchsupporting
confidence: 75%
See 1 more Smart Citation
“…For instance, Oberweis and Bradford (2017) reported that student veterans in their study expressed a strong need for academic counseling. Killam and Degges-White (2018) noted that the academic challenges that student veterans experienced may be related to the differences between the academic and military environments. They stated that learning and teaching in higher education is less regimented and constrained than in the military.…”
Section: Today's Veterans' Needsmentioning
confidence: 99%
“…Although adjusting to academia's culture, processes, and requirements were issues that also impact civilian students (e.g., first-generation); student veterans, as noted by Killam and Degges-White (2018), were more likely to be reluctant to seek assistance or ask for help from faculty, staff, or fellow students. They also found that student veterans typically enrolled in colleges near their military discharge location, rather than in their hometowns, where they may have had connections with persons and programs that assist youth in applying for and adapting to college.…”
Section: Today's Veterans' Needsmentioning
confidence: 99%